Relationship between Personality Traits and Humor Styles and their Impact on Social Support of Young Adults - Arshad, Rabika tul Ain; Younas, Nadia; Zahra, Mehdia (Journal of Applied Research and Multidisciplinary Studies, 2025)
The current study aimed to investigate the relationship between light and dark triad of personality traits corresponding with healthy and unhealthy humor styles. Furthermore, it also assessed the impact of light and dark triad of personality traits as well as self-enhancing, affiliative, aggressive, and self-defeating humor styles on the social support of young adults. A quantitative study design was employed. A total of 214 participants were purposively selected from various public sector universities. Standardized instruments, namely Light Triad Scale (LTS), Short Dark Triad (SD3), Humor Styles Questionnaire (HSQ-32), and Multidimensional Scale of Perceived Social Support were utilized for data collection. The data was statistically analyzed using correlation, regression, and t-test. The results showed that significant inverse relationship exists between light triad of personality and affiliative humor style. There is a positive correlation between aggressive humor and light triad traits. Dark triad traits are directly associated with self-enhancing, aggressive, and self-defeating humor styles, however, not with affiliative humor style. The exploration of gender differences revealed that men tend to score higher than women in light triad of personality. Likewise, men score significantly higher in aggressive humor style, whereas women score higher in perceived social support. The multiple linear regression results manifest that self-enhancing humor positively predicts social support, whereas self-defeating humor has negative impact on social support of the young adults.